Handbook of evidence-based therapies for children and adolescents : bridging science and practice - Steele, Ric G.; Elkin, T. David; Roberts, Michael C. (Issues in clinical child psychology., 2008)
Intended for clinical child, school, and counseling psychologists; clinical social workers; and child psychiatrists, this book provides advanced clinical and counseling psychology programs. It offers evidence-based therapies for the covered disorders, and case examples, tables, and reference lists.